Sociodemographic index–age differences in the global prevalence of cardiovascular diseases, 1990–2019: a population-based study - Xunliang Li; Channa Zhao; Mengqian Liu; Wenman Zhao; Haifeng Pan; Deguang Wang (Archives of Public Health)
Abstract Background This study aims to assess the global burden and trends in cardiovascular diseases (CVDs) prevalence, stratified by sociodemographic index (SDI) categories and age groups, across 204 countries and territories. Methods Utilizing data from the Global Burden of Disease Study 2019, this study analyzed trends in the age-standardized prevalence rate of overall and type-specific CVDs, including rheumatic heart disease, ischemic heart disease, stroke, hypertensive heart disease, non-rheumatic valvular heart disease, cardiomyopathy and myocarditis, atrial fibrillation and flutter, peripheral artery disease, endocarditis, and other cardiovascular and circulatory diseases. Age-standardized prevalence rates were stratified by SDI categories (low, low-middle, middle, high-middle, and high) and age groups (0–14, 15–49, 50–69, and ≥ 70 years). The corresponding average annual percentage change was calculated to assess temporal trends. Results From 1990 to 2019, the global age-standardized prevalence rate per 100,000 population for CVD decreased from 6728.04 (95% UI 6394.55 to 7059.66) to 6431.57 (95% UI 6109.95 to 6759.8), with an average annual percent change of -0.15% (95% CI -0.17 to -0.13). When stratified by SDI category, the age-standardized prevalence rate of CVD decreased significantly in high-middle and high SDI countries but increased in middle, low-middle, and low SDI countries. By age group, the age-standardized prevalence rate of CVD declined in the 50–69 and ≥ 70 years groups but increased in the 0–14 and 15–49 years groups. SDI levels were negatively associated with faster increases in the age-standardized prevalence rate of CVD across all ages and age groups. Low SDI countries consistently showed the highest age-standardized prevalence rates of CVD in the younger age groups (0–14 and 15–49 years), while high-middle SDI countries had the highest rates in the older age groups (50–69 and ≥ 70 years). The age-standardized prevalence rate of CVD was negatively associated with SDI levels in the 0–14 and 15–49 years groups and positively associated with SDI levels in the 50–69 and ≥ 70 years groups. Type-specific CVDs such as rheumatic heart disease, other cardiovascular and circulatory diseases, non-rheumatic valvular heart disease, and hypertensive heart disease showed increased age-standardized prevalence rates from 1990 to 2019. Conclusions This study highlights significant disparities in CVD prevalence across sociodemographic and age groups. While the global prevalence of CVD has generally decreased, the rise in CVD prevalence in lower SDI countries and younger populations calls for tailored intervention strategies. Addressing these disparities is crucial to mitigating the growing burden of CVD and promoting cardiovascular health on a global scale.